The November 2012 general strike and anti-austerity protests – analysis from the Portuguese case - Dias, H.; Fernandes, L. C. (Workers of the World: International Journal on Strikes and Social Conflict, 2016)
Opposition against austerity was the cornerstone to the protests which took place in since 2010. In Portugal, the first signs of mobilization came from the unions, although the emergence of new actors allowed the movement to be socially amplified. This article reflects on the 14th of November 2012 general strike to, from the Portuguese case, explore its insertion in this period's contentious politics, not only as to its transnational dimension – within the European Union framework -, but also as to the relationship between actors – particularly between unions and the new political actors. While facing a political agenda set on producing major changes in the social and labour regime, unions found increased challenges in the use of their ultimate instrument of struggle – strikes -, specially considering its power bases, already quite weakened before this mobilization cycle.